Supporting Information Tasks with User-Centred System Design: The Development of an Interface Supporting Bioinformatics Analysis - Bartlett, Joan C.; Neugebauer, Tomasz (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
We present an interface to support the integration of bioinformatics analysis with scientific practice. The interface guides scientists through the co-ordinated use of a wide range of analyses and resources in order to solve a complex information task. Nous présentons une interface qui utilise l’intégration de l’analyse bio-informatique dans le domaine scientifique. Cette interface guide les scientifiques à travers l’utilisation coordonnée d’une vaste gamme d’analyses et de ressources, de manière à effectuer une tâche informationnelle complexe.